Predicting guest satisfaction and willingness to pay premium prices for green hotels - Jin Yang; Mohammad Nurul Hassan Reza; Abdullah Al Mamun; Muhammad Mehedi Masud; Mara Ridhuan Che Abdul Rahman (Humanities & Social Sciences Communications)
Abstract Green transformation in the hotel industry represents an undeniable trend yet poses financial challenges, particularly in emerging economies. Expanding on the service quality-satisfaction-behavioral intention paradigm, this study investigates the influences of green emotional attachment, attitude towards green hotels, green image, green practice performance, word-of-mouth, guest satisfaction, functional value, and green experiential loyalty on green hotel premium payment. We collected 573 data points from China using purposive sampling. Partial least squares structural equation modeling was used to analyze the data. The findings revealed the positive effect of attitudes towards green hotels and green practices on guest satisfaction. The findings confirmed a positive correlation between guest satisfaction and willingness to pay a premium price for green hotels. This study also confirms the moderating effect of green experiential loyalty. Moreover, it recognizes gender, age, and income as partial moderating factors. These findings offer valuable insights into green hotel consumption research and assist practitioners in enhancing guest willingness to pay premiums and fostering sustainable industry development. The active implementation of strategies to boost guest satisfaction and willingness to pay premiums can further environmental conservation and support zero-carbon goals in the hospitality sector.